Internalisasi Wawasan Kebangsaan Dalam Mata Pelajaran Pendidikan Agama Buddha Dan Budi Pekerti (Studi Fenomenologi Pada Peserta Didik Kelas Ix Di Sekolah Menengah Pertama Swasta (SMPS) - Yayang Hadi Kusno (STABN Sriwjaya, 2023)
The problem raised in this study is that the internalization of nationalism in Buddhist Religious Education Subjects is unknown. The purpose of this study is to describe the internalization of nationalism insights in Buddhist Religious Education Subjects. This research uses a qualitative approach with phenomenological method. The informants in this study were principals, educators, and 9th grade students of SMPS Perguruan Buddhi Tangerang in the 2022/2023 school year. The data collection techniques used in this study were observation, interview, and documentation. The data analysis technique used in this research is the data analysis technique model of M.B. Miles, A.M. Huberman, and Johny Saldaña (1994). The results in this study show that the internalization of nationalistic insight is defined as a process of stages or series in the introduction, planting, coaching, and strengthening in a sustainable and in-depth information, messages, and noble values concerning nationalism. Teaching materials on nationalistic insight in Buddhist Religious Education subjects are sourced from the Dhammapada book, Paritta book, and Buddhist Religious Education book class IX. The cultivation of knowledge about national insight that has been carried out by educators is by showing politeness, giving greetings to each other at holiday celebrations, greetings of anjali attitude and Namo Buddhaya. Efforts to internalize national insight in Buddhist Education subjects carried out by educators are by introducing, instilling, guiding and strengthening the noble values of Dhamma that are in line with national insight. The practice or example done by educators and students in internalizing national insight is by practicing the rules of school discipline, ethics, and norms in the practice of national insight both in the classroom, cetiya, and outside the classroomThe problem raised in this study is that the internalization of nationalism in Buddhist Religious Education Subjects is unknown. The purpose of this study is to describe the internalization of nationalism insights in Buddhist Religious Education Subjects. This research uses a qualitative approach with phenomenological method. The informants in this study were principals, educators, and 9th grade students of SMPS Perguruan Buddhi Tangerang in the 2022/2023 school year. The data collection techniques used in this study were observation, interview, and documentation. The data analysis technique used in this research is the data analysis technique model of M.B. Miles, A.M. Huberman, and Johny Saldaña (1994). The results in this study show that the internalization of nationalistic insight is defined as a process of stages or series in the introduction, planting, coaching, and strengthening in a sustainable and in-depth information, messages, and noble values concerning nationalism. Teaching materials on nationalistic insight in Buddhist Religious Education subjects are sourced from the Dhammapada book, Paritta book, and Buddhist Religious Education book class IX. The cultivation of knowledge about national insight that has been carried out by educators is by showing politeness, giving greetings to each other at holiday celebrations, greetings of anjali attitude and Namo Buddhaya. Efforts to internalize national insight in Buddhist Education subjects carried out by educators are by introducing, instilling, guiding and strengthening the noble values of Dhamma that are in line with national insight. The practice or example done by educators and students in internalizing national insight is by practicing the rules of school discipline, ethics, and norms in the practice of national insight both in the classroom, cetiya, and outside the classroom